STATE PATRONAGE TO TWO SHAIVITE MATHS OF THE EAST: JANGAMBARI MATH OF BANARAS & MATH AT BODH GAYA - Rahman Khan, Mohd. Motiur (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The paper narrates the story of two prominent Shaiva monasteries who enjoyed madad-i ma ‘ash grants from the Mughals. One of them was the sole custodian of the famous Mahabodhi Temple. Another became a successful banker for the region apart from their usual activities of imparting specialised knowledge in the Shaiva system. The Mughal grants became institutions and survived the Colonial rule. The institutions struggled and tried to adapt to the new situation and continued their activities. Thus, giving us a glimpse into the functioning and management of medieval Indian institutions that continued their activities and their traditional role in society under different dispensations, namely, Mughals, British and then Independent India.